Demystifying mysticism: a comparative study of the poetry of William Blake and Rabindranath Tagore - Samantaray, Swati (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Mysticism is often accepted as a spiritual quest for the hidden truth or wisdom, the goal of which is union with the transcendent realm. Mystic experiences are said to be unique for each individual. Yet we find that there is a marked resemblance between the experiences of mystics, not merely of the same race or cult, but also of diverse social orders and religions. This paper discusses the concept and perception of mysticism in the works of the occidental poet William Blake and the oriental poet Rabindranath Tagore. Born in different lands they seemed to share a spiritual affinity. William Blake’s works, though largely Biblical in its imagery, is apocalyptic in style and scope. In Indian mystical thought, Tagore offers a system in which the theism of the Bhagavad Gita, the metaphysics of the Vedas, the Upanishads, the mysticism of the Bauls and the philosophical principles of Vaishnavism and Sufism exist in synthesis. An in-depth study of their works reveals that, the poetic vision of Blake and Tagore coalesce notwithstanding the kaleidoscopic divergence by studying their poetic art, craft and oeuvre, while casting off the cultural tensions and nationalistic pretensions aside. The most prominent theme in their poetic works is that of mysticism and transcendentalism. Though their ways of depicting this is very different and diverse and their symbolism is also at variance, yet their poems bear a similar thematic purpose, which is mysticism.